GAMBARAN PENGASUHAN IBU DALAM MENGEMBANGKAN PERILAKU ADAPTIF SISWA TUNAGRAHITA - Rishanty, Rani; Pandia, Weny Savitry S. (Jurnal Psikologi, 2018)
The purpose of this study is to describe mother’s parenting in developing adaptive ability on children with moderate to severe mental retardation. This research was a qualitative research. The subjects were three mothers who have children with moderate to severe mental retardation at SDLB X Jakarta. The subjects were selected using purposive sampling technique. Data were collected using interview and observation. The observation data was only used to support the suitability of interview data. The results showed that three participants had less positive parenting in developing students' adaptive abilities. This was shown from the acceptance and demandingness of the mother to each child. Three participants taught with verbal and provide direct assistance to student. This situation happens when students was unable to perform daily activities. The subjects also had no specific rules and consequences to support students' adaptive skills. Several factors that influence those condition were unappropriate expectation of mothers with their children and limited knowledge about characteristic of children with mental retardation. Thus, some areas of students' adaptive ability didn’t grow optimally.